Street murmurs : intangible streets of Singapore - Chang, Valantia Wei Tong (Nanyang Technological University, 2020)
The streets that we have grown accustomed to in Singapore have lost their significance over time. Traditionally, these streets were used and identified in remarkably distinctive ways by different generations. This had created intangible street names and valuable stories that were passed down from generation to generation via word of mouth. However, gone are the days when Singapore’s current generation have much knowledge of these streets today.There is an urgent need to extract and collect stories from Singapore’s current silver generation that still retains the knowledge of these names and associated stories. The research aims to uncover the effect that personal stories have on intangible street heritage in Singapore. It intends to create separate mediums that could enable such stories and experiences to continue to be passed down through greater outreach. Through this documentation, the project endeavours to preserve and appreciate local streets and contribute to both Singapore’s heritage and history.